2020
DOI: 10.1002/lipd.12271
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein Impairs Triglyceride Clearance via Androgen Receptor in Male Mice

Abstract: Elevated postprandial triacylglycerols (TAG) are an important risk factor for cardiovascular disease. Men have higher plasma TAG and impaired TAG clearance compared to women, which may contribute to sex differences in risk of cardiovascular disease. Understanding mechanisms of sex differences in TAG metabolism may yield novel therapeutic targets to prevent cardiovascular disease. Cholesteryl ester transfer protein (CETP) is a lipid shuttling protein known for its effects on high-density lipoprotein (HDL) chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 66 publications
0
16
0
2
Order By: Relevance
“…We recently demonstrated that CETP impairs postprandial TG clearance in males through liver androgen receptor signaling (Palmisano et al, 2020). Since LDLR is a major determinant of plasma TG clearance, LDLR may play a role in CETP‐mediated regulation of TG clearance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that CETP impairs postprandial TG clearance in males through liver androgen receptor signaling (Palmisano et al, 2020). Since LDLR is a major determinant of plasma TG clearance, LDLR may play a role in CETP‐mediated regulation of TG clearance.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic CETP mice were purchased from the Jackson Laboratories (C57BL/6‐Tg(CETP)UCTP20Pnu/J, Strain: 001929, Jackson Laboratories). We previously established the role of CETP on TG metabolism in both males and females relative to WT mice (Palmisano et al, 2016, 2020). LDLR deletion has been shown to impair TG clearance and increase TG production, contributing to elevated TGs relative to WT mice (Coenen et al, 2007; Ishibashi et al, 1996; Teusink et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations